A Bibliometric Study of Mosque Literature in Reputable International Journals - Muhammad Nabahan Azizy (Perkumpulan Ahli Manajemen Dakwah Indonesia (PAMDI), 2025)
Purpose – This article aims to map studies on mosques published in Scopus between 2014 to 2023. Design/methodology/approach – A bibliometric approach was used in four steps: determining keywords and extracting article data using Publish or Perish (PoP), selecting and processing articles, processing Digital Object Identifier (DOI), and presenting the findings. Findings – Malaysia has been a leading contributor to the field of mosque studies, as evidenced by its dominance in terms of geographical distribution, institutional affiliation, and the authorship of scholarly works in this area. The mapping of studies was distributed across five primary subjects: architecture, building design, Malaysia, Muslim life, and mosque design methodology. Consequently, the field of mosque studies has been predominantly shaped by architectural scholarship in the past decade. Research implications – Mosques should prioritize aesthetic appeal and practical functionality as places of worship and community centers. Future researchers must expand the scope of inquiry beyond mere worship to encompass the multifaceted functionality of mosques. The implementation of optimal strategies facilitates the establishment of a societal framework that originates within the confines of the mosque. Originality/value – The field of mosque studies has undergone significant expansion; however, the existing literature is predominantly organized by thematic categories. Paper type Research paper